Topika kwartetów smyczkowych Zbigniewa Bujarskiego, Krzysztofa Pendereckiego i Marka Stachowskiego - Wójtowicz, Ewa (Res Facta Nova, 2025)
The subject under discussion in this article is string quartets by three Polish composers from the same generation: Krzysztof Penderecki (1933–2020), Zbigniew Bujarski (1933–2018) and Marek Stachowski (1936–2004). The author defines the fundamental topoi of the quartet genre: conversationality, the “speech” style and the “singing” style, and then finds their manifestations both in works from the 1960s and 1970s, which lay within the circle of sonorism, and in later works composed using more traditional means. Among other historical conventions, the pastoral style, which gained original updates through the sonorist technique, was taken into account, as well as topics characteristic of the composers’ individual styles. A special feature of Bujarski’s music are the voices of birds, appearing both in works with religious themes (Quartet for Advent), as well as compositions in which the composer engages in reflections of an existential nature (Quartet for a House-Warming, Quartet for Autumn). Marek Stachowski’s quartet technique is distinguished by the use of fugato to achieve the effect of “unravelling” the music, highlighting the expression of movement. This composer’s Musica festeggiante offers an example of introducing an extended fugue into the form of the piece. The article concludes with an attempt to interpret the meanings carried by music featuring folk intonations. In Bujarski’s works, this is part of his strategy of punctuating quartets with non-musical titles, while in Penderecki’s late works the period of childhood is introduced – in a similar way to quotation – giving Quartet No. 3 “Leaves From an Unwritten Diary” and String Quartet No. 4 an autobiographical touch.